Pola Sidik Jari dan Besaran Sudut Axial Triradius Digital (ATD) pada Pengguna Narkotika Jenis Shabu-Shabu di Kota Palembang - Mundijo, Trisnawati; Pramayastri, Vina; Febiyolan, Febiyolan (MAGNA MEDICA Berkala Ilmiah Kedokteran dan Kesehatan, 2020)
Fingerprint Pattern and Digital Axial Triradius (ATD) Angle on Shabu-Shabu Narcotics Users in Palembang CityBackground: Dermatoglyphics is a science to determine a pattern both from fingerprints, triradius, tendrils, and the Axial Triradius Digital (ATD) angle. Nowadays, it is can be used in ethnhobiology, forensic or to determine the pattern the disease or disorder. Research on dermatoglyphics is still needs study. Today, research on fingerprint patterns, especially in drug cases is still very limited.Objective: To find out what is the dominance of the fingerprint pattern and ATD angle in people with drug cases.Method: The research was conducted in the National Narcotics Agency (BNN) of South Sumatra and the Cahaya Putra Rehabilitation Foundation in Palembang, South Sumatra. Samples were carried out by total sampling from the two places was 30 peoples, all of whom were drug users of the type of methamphetamine. Fingerprint pattern data were collected using the U.Are.U Digital Personal tool. Fingerprint reader attaches the fingerprints of the ten fingers, while the ATD angle calculation is done by smearing lipstick on both palms of the sample and pasting them on the observation sheet. The data obtained were analyzed.Result: The fingerprint patterns were at most with a whorl pattern of 99 fingers (41.25%). Whereas for the ATD angle, the highest results were obtained at angles> 50o from both hands as many as 14 people (58.3%).Conclusion: The most dermatoglyphic characteristics of drug users are whorl patterns with an ATD angle> 50o.